C60-Fullerenes: detection of intracellular photoluminescence and lack of cytotoxic effects - Carroll David L; Lively Mark O; Hantgan Roy R; Levi Nicole; Prasad Gaddamanugu L (Journal of Nanobiotechnology, 2006)
Abstract We have developed a new method of application of C60 to cultured cells that does not require water-solubilization techniques. Normal and malignant cells take-up C60 and the inherent photoluminescence of C60 is detected within multiple cell lines. Treatment of cells with up to 200 μg/ml (200 ppm) of C60 does not alter morphology, cytoskeletal organization, cell cycle dynamics nor does it inhibit cell proliferation. Our work shows that pristine C60 is non-toxic to the cells, and suggests that fullerene-based nanocarriers may be used for biomedical applications.